Transforming schools for multilingual learners a comprehensive guide for educators - Zacarian, Debbie (Thousand Oaks, California Corwin, 2023)
"The first edition of this book (entitled "Transforming Schools for English Learners") offered a practical guide to transforming schools into places in which Multilingual Learners (MLs) are valued, affirmed and able to reach their highest potential. Its target audience, building and central office administrators appreciated its practicality and comprehensive coverage of everything from program model selection to evidence based practices for promoting language development in the context of learning academic content. Since the publication of the first edition, new research and developments in practice have furthered our understanding of how to effectively lead schools for Multilingual Learner success. These include: 1. A more nuanced understanding of the socicultural underpinnings of language development, influenced by research from psychiatry, social work, and education. 2. A shift from deficit to asset-based models that affirm the value of multilingualism as well as multilingual families' funds of knowledge. 3. A greater appreciation of the importance of both culturally responsive instruction and social emotional learning. 4. Increased awareness of the presence and influence of ACES -- particularly among undocumented children and their families and unaccompanied minors who live in chronic fear of deportation as well as families who have fled civil crises and war in their homelands. In addition, major federal and state policy shifts (e.g., ESSA, Proposition 58 in California), compounded by the impact of the pandemic on MLs and their families have dramatically changed the playing field"--
Includes bibliographical references and index.
Keywords: English language -- Study and teaching -- United States -- Foreign speakers; School management and organization -- United States